Effect of calcium chloride marination on bovine Cutaneus trunci muscle - Gonzalez, Claudia Beatriz; Salitto, Valeria A.; Carduza, Fernando Jose; Pazos, Adriana Alejandra; Lasta, Jorge Augusto (Elsevier, 2019)
The aim of this investigation was to determine the possibility of using calcium chloride solution in tough muscles (Cutaneus trunci) to reduce the aging period required to increase tenderness, without introducing undesirable ¯avors. Muscles were marinated n 0.25 M CaCl2 solution for 2 h and after that aged for 0, 1, 2, 3, 4, 5 and 7 days. Tenderness was evaluated by the myo®brillar fragmentation index (MFI), Warner Bratzler shear force (WBS) and sensory panel evaluation. MFI values showed signi®cant dif- ferences between treated and control samples aged for 1, 2 and 3 days (P<0.05). MFI values of treated samples aged 3 days were similar to those obtained for the control samples but aged seven days. WBS values were not signi®cantly di erent between samples. Consumer panelists preferred treated samples aged 3 days to the control ones aged 7 days. It was concluded that calcium chloride treatment can be used in Cutaneus trunci muscle to reduce the aging time required to increase tenderness. # 2000 Elsevier Science Ltd. All rights reserved.